On the Strain Rate Sensitivity of Fibre-Reinforced Self-Compacting Concrete - PAJĄK, Małgorzata; JANISZEWSKI, Jacek (Engineering Transactions, 2022)
The present paper deals with the SCC reinforced with the recycled fibres and their combination with the polypropylene fibres subjected to high strain rates. Using the SHPB technique, the strain rate sensitivity of the mixtures was determined in the range of strain rates from 140 to 200 s-1. It was found that the strain rate dependence of both types of mixtures was comparable. The failure pattern affirmed the role of fibres in carrying the loads for the strain rates about 100 s-1. For the highest strain rates occurrence of fibres in the mixture was less important.